To What Extent is Virtual Reality Therapy Efficient as A Treatment of Social Anxiety Disorder? (British Journal of Multidisciplinary and Advanced Studies, 2023)
The effectiveness of virtual reality therapy as a therapeutic intervention for individuals with social anxiety disorder is investigated in this study. This research was created using a meta-analytical method and a review of several studies and conclusions by prior experts. It seeks to obtain a better knowledge of how virtual reality treatment impacts key symptoms and indications of social anxiety disorder, such as self-esteem and social interaction abilities. It also contributes to the current body of research and advances understanding of virtual reality therapy's potential as a cutting-edge, effective treatment for psychiatric issues. The study also incorporates culturally sensitive adaptations to VR therapies that take into consideration individuals' diverse cultural backgrounds. Additionally, the study looks at VR therapy's cost, flexibility, and economic factors. In conclusion, this research paper offers a thorough grasp of the possible uses and restrictions of virtual reality treatment.